An autonomous underwater vehicle with a canard rudder for underwater minerals exploration - Yoshida, Hiroshi; Hyakudome, Tadahiro; Ishibashi, Shojiro; Sawa, Takao; Nakano, Yoshiyuki; Ochi, Hiroshi; Watanabe, Yoshitaka; Nakatani, Takeshi; Ota, Yutaka; Sugesawa, Makoto; Matsuura, Masami (2013 IEEE International Conference on Mechatronics and Automation, 2013)
Exploration and mining of natural resources in the region of seabed are needed for lasting economic growth, because an abundance of natural resources, including rare metal, is in Japan's exclusive economic zone (EEZ). The cost down of exploration and mining is an important issue for industrialization. It is well known that unmanned and/or autonomous platforms for exploration are effective to reduce operation cost. JAMSTEC has developed a cruising type autonomous underwater vehicle (AUV) to perform exploration in hydrothermal activity areas up to depth of 3,000 meters since 2011. This specified purpose AUV (5 m long, 2.7 tons in weight) has capability of high maneuverability for eliciting high performance of sonars and is equipped with three sonars: a synthetic aperture sonar (SAS), an interferometry sonar (IFS) and a sub-bottom profiler (SBP). The cruising AUV, named Yumeiruka, is thus has a canard rudder to maintain a fixed posture in horizontal and vertical plane. In March 2013 the 15-days sea trial of the vehicle was carried out in the Sagami Bay and we achieved constant pitch control by using the canard rudder during an altitude change.